Emerging trends and challenges in corporate governance in America: A 2023 perspective - Dami, Albert; Kim, Stephen (Journal of Economics and Business Letters, 2023)
This paper provides a comprehensive analysis of the current state and emerging trends in corporate governance within American corporations, focusing on the year 2023. It examines the evolving landscape of corporate governance in response to technological advancements, regulatory changes, and shifting societal expectations. Through a detailed review of literature and analysis of case studies, this study highlights the significant challenges and opportunities facing boards of directors, including the integration of environmental, social, and governance (ESG) criteria, the impact of digital transformation, and the evolving role of stakeholders. The findings underscore the necessity for American corporations to adapt to a rapidly changing environment, emphasizing the importance of transparency, accountability, and sustainability in corporate governance practices.